2021
DOI: 10.1002/jclp.23164
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported emotion regulation difficulties in psychosis: Psychometric properties of the Difficulties in Emotion Regulation Scale (DERS‐16)

Abstract: Objective: Individuals with psychosis self-report difficulties in understanding, relating, and responding to emotions as treatment priorities, yet we lack comprehensive, reliable, and valid assessments for routine clinical use. Methods: The psychometric properties of a brief version of the Difficulties in Emotion Regulation Scale-16 (DERS-16) were examined using anonymized data from a sample of 150 outpatients with psychosis. Results: Confirmatory factor analysis supported the fivefactor structure of the DERS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…Higher scores reflect greater ER difficulties. It demonstrates good internal consistency, test–retest reliability, convergent and discriminant validity, and responsiveness to ER interventions in various samples, and its internal consistency and convergent validity are supported with individuals in psychosis (Lawlor, Vitoratou, Hepworth, & Jolley, 2021).…”
Section: Methodsmentioning
confidence: 98%
“…Higher scores reflect greater ER difficulties. It demonstrates good internal consistency, test–retest reliability, convergent and discriminant validity, and responsiveness to ER interventions in various samples, and its internal consistency and convergent validity are supported with individuals in psychosis (Lawlor, Vitoratou, Hepworth, & Jolley, 2021).…”
Section: Methodsmentioning
confidence: 98%
“…Tis study discovered a signifcant negative correlation, with a 6.5% decrease in DERS-16 scores as age increased. Studies in the literature have shown that DER tends to decrease with age [30,31] while others have suggested that age is not a distinguishing factor in emotion regulation [32,33]. Te observed decrease in DER scores with age could potentially be attributed to increased life experience and maturity, which contribute to better emotional control.…”
Section: Discussionmentioning
confidence: 98%
“…Individuals with psychosis, as compared to nonclinical controls, report difficulties in identifying, understanding, and accepting their emotions, engaging in goal-directed behavior, and being willing to experience negative emotions in the pursuit of meaningful activities (Lawlor et al, 2021). In addition, it has been found that people with schizophrenia have difficulty controlling impulses when experiencing negative emotions and accepting emotional responses (Moritz et al, 2010; O’Driscoll et al, 2014; van der Meer et al, 2014; Westermann & Lincoln, 2011).…”
Section: Discussionmentioning
confidence: 99%